Assessing Health Status of Gajahwong River Ecosystem in Yogyakarta City through Biomonitoring and Community Empowerment - Eka Sulistiyowati; Dien F Awaliyah (School of Postgraduate Studies, Diponegoro Univer, 2025)
Research on river health assessment using biomonitoring with community empowerment through citizen science remains limited. This study aims to evaluate river health using biological indicators while fostering community involvement in data collection and analysis. The study focuses on the Gajahwong River in Yogyakarta City, an urban river undergoing changes due to urbanization. The methodology includes river health assessment based on macroinvertebrate biomonitoring, diversity index calculations, and a qualitative evaluation of the Citizen Index of Ecological Integrity (CIEI). Additionally, water quality data from the Environmental Agency (DLH) were analyzed as a comparison to community-collected data. Overall, the results indicate that the biological index falls under the moderately polluted category, consistent with abiotic parameter measurements (nitrate and phosphate), which also indicate pollution. Meanwhile, the CIEI reflects the community's perception of the ecological condition of the Gajahwong River, classifying it as moderate.